Implementation of Electronic Customer Relation Management (ECRM) Program in Shaping Positive Word of Mouth at PT Mandiri Utama Finance - J.A Wempi; Estriastuti Nur Aisyah; Aas sulistia indriani (Eduvest - Journal of Universal Studies, 2025)
PT Mandiri Utama Finance (MUF), as the youngest automotive financing company in Indonesia, has successfully recorded assets exceeding IDR 10 trillion and competes with major players in the industry. However, the company experienced a significant decline in financing volume, not only among new consumers but also within the Additional Order (AO) and Repeat Order (RO) segments, which are vital components of MUF’s customer ecosystem. This downturn is also reflected in the declining scores of the Customer Satisfaction Index (CSI) and Net Promoter Score (NPS). This study aims to explore the implementation of the Electronic Customer Relationship Management (E-CRM) program in shaping Positive Word of Mouth (PWOM) among MUF customers. Using a descriptive case study method with a qualitative approach, this research employs data analysis and in-depth interviews with key personnel involved in the E-CRM system. The theoretical framework is based on Lasswell’s communication model (Who Says What In Which Channel To Whom With What Effect) to map MUF's communication strategies, and the Stimulus-Response Theory to explain how digital messages influence customer behavior through prior interactions and experiences. The findings reveal that the suboptimal integration of the E-CRM system and the limited consumer engagement initiatives, such as loyalty programs and testimonial-driven campaigns, hinder the spread of PWOM. This research offers practical insights into enhancing customer-centered digital communication strategies.